Pelaksanaan Kebijakan Penurunan Stunting di Kabupaten Solok Tahun 2023 - Nanda, Arastika; Yusran, Rahmadani (Journal of Civic Education, 2024)
This research investigates the implementation of stunting reduction policies in Solok Regency. The findings reveal that the local government has initiated several programs aimed at improving food consumption patterns, raising nutritional awareness, enhancing the quality of nutrition and services, and strengthening the food and nutrition monitoring system. A qualitative research method with a descriptive approach was employed to analyze and interpret public policy information. The study's informants included representatives from regional apparatus organizations (OPD), the Task Force for Accelerating Stunting Reduction, the Women's Empowerment and Child Protection Agency (DPPKBP3A), the Community Empowerment and Village Service, and the Stunting Reduction Acceleration Team. The research identifies key challenges in the implementation process, such as inadequate facilities and infrastructure, low remuneration for health workers, a shortage of human resources, and limited budget allocations. To ensure the program's effectiveness, the local government should establish both long-term and short-term strategies.